2015
DOI: 10.1111/dom.12578
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and metabolic changes with sodium‐glucose co‐transporter 2 inhibition

Abstract: Sodium-glucose co-transporter 2 (SGLT2) inhibitors are the latest addition to the class of oral glucose-lowering drugs. They have been rapidly adopted into clinical practice because of therapeutic advantages, including weight loss and reduction in blood pressure, in addition to glycaemic benefits and a low intrinsic risk of hypoglycaemia. Although there are extensive data on the clinical effects of SGLT2 inhibition, the metabolic effects of inhibiting renal glucose reabsorption have not been fully described. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 86 publications
1
73
0
2
Order By: Relevance
“…Rajeev et al 85 have reviewed possible explanations, such as a compensatory increase in food intake, but the mechanism is uncertain. Ferrannini et al 86 reported that patients in an empagliflozin trial lost only 38% of the weight loss predicted from the calories lost via glycosuria, and suggested that this was due to an increase in food intake.…”
Section: Empagliflozinmentioning
confidence: 99%
“…Rajeev et al 85 have reviewed possible explanations, such as a compensatory increase in food intake, but the mechanism is uncertain. Ferrannini et al 86 reported that patients in an empagliflozin trial lost only 38% of the weight loss predicted from the calories lost via glycosuria, and suggested that this was due to an increase in food intake.…”
Section: Empagliflozinmentioning
confidence: 99%
“…These two relatively new antidiabetic agents, ipragliflozin and sitagliptin, have been widely used in Japan. The two agents are known to have multiple benefits other than glucose‐lowering effects (Appendix S1); however, there have been few head‐to‐head studies comparing the pleiotropic effects of SGLT2 inhibitors and DPP‐4 inhibitors. In the present study, we performed a prospective randomized controlled study to compare the efficacy and safety profiles of ipragliflozin and sitagliptin.…”
Section: Introductionmentioning
confidence: 99%
“…4 These two relatively new antidiabetic agents, ipragliflozin and sitagliptin, have been widely used in Japan. The two agents are known to have multiple benefits other than glucose-lowering effects (Appendix S1) [5][6][7][8] ; however, there have been few head-to-head studies comparing the pleiotropic effects of SGLT2 inhibitors and DPP-4 Y. Tsurutani and K. Nakai contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, SGLT2 inhibition promotes significant energy loss through glycosuria, which causes weight loss 53. This is evident within 4 weeks of treatment but continues for up to 102 weeks in the longer duration trials 54,55.…”
Section: Methodsmentioning
confidence: 77%